Development of customised wheelchair racing gloves using digital fabrication techniques - Covill, D.; King, R.; Townsend, J.; Brickley, G.; Drouet, J. M. (Proceedings, 2020)
Wheelchair racing gloves are typically solid 3D structures held in a clenched fist which help to propel the chair by pushing the glove against a rotating rail which is attached to the wheel to drive the wheelchair forward. There has been a recent movement towards developing customisable gloves using 3D scanning technique, however, currently there are no commercial offerings which allow for product customisation without being prohibitively expensive. The aim of this project, therefore, was to develop a scalable method for producing customised wheelchair racing gloves in a cost-effective way. The generated 3D forms were 3D printed in a variety of infill densities and finished with a grip liner. These 3D printed gloves were compared in terms of fit and perception of performance, and for their mass, cost and energy/power cost. The 3D printed gloves provided a substantially reduced mass with only a minimal reduction in overall strength at a comparable cost to the solid equivalent.